The Influence of Organizational Climate, Communication Competence and Work Motivation On The Performance Of Sumut Syariah Bank Employees Based On Islamic Education In North Sumatra - Lasahido, Nurrahmi; Lubis, Lahmuddin; Wijaya, Candra (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research is to find outThe influence of organizational climate, communication competence and work motivation on the performance of North Sumatra Sharia Bank employees in North Sumatra. This research uses quantitative methods, with a form of descriptive research that processes data using the results of distributing questionnaires to population samples, so as to obtain a significant relationship and a mutual tendency towards the probability of error regarding the hypothesis being built. This type of research approaches path analysis (path analysis). The results of this research are: 1. Organizational climate has a direct positive effect on work motivation at Bank Sumut Syariah in North Sumatra by 8%. 2. Communication competency has a direct effect on work motivation at Bank Sumut Syariah in North Sumatra by 11.2%. 3. Organizational climate has a direct effect on employee performance at Bank Sumut Syariah in North Sumatra by 11.9%. 4. Communication competency has a direct effect on employee performance at Bank Sumut Syariah in North Sumatra by 12.6%. 5. Work motivation has a direct effect on employee performance at Bank Sumut Syariah in North Sumatra by 11%. 6. Organizational climate has an indirect effect on employee performance at Bank Sumut Syariah in North Sumatra through work motivation of 1.5%. 7. Communication competency has an indirect effect on employee performance at Bank Sumut Syariah in North Sumatra through work motivation of 0.8%. Work motivation has a direct effect on employee performance at Bank Sumut Syariah in North Sumatra by 11%. 6. Organizational climate has an indirect effect on employee performance at Bank Sumut Syariah in North Sumatra through work motivation of 1.5%. 7. Communication competency has an indirect effect on employee performance at Bank Sumut Syariah in North Sumatra through work motivation of 0.8%. Work motivation has a direct effect on employee performance at Bank Sumut Syariah in North Sumatra by 11%. 6. Organizational climate has an indirect effect on employee performance at Bank Sumut Syariah in North Sumatra through work motivation of 1.5%. 7. Communication competency has an indirect effect on employee performance at Bank Sumut Syariah in North Sumatra through work motivation of 0.8%.